FUTURE PACKAGE FINANCING PRODUCTS WITH AKAD MURABAHAH IN THE PERSPECTIVE OF SHARIA ECONOMIC LAW - Zainul Arif Andalusi (AHKAM : Jurnal Ilmu Syariah, 2019)
This research is including legal research, with descriptive qualitative design. The primary data source of this study is Law No. 21 of 2008, Bank Indonesia Regulation No. 07/46/PBI/2005 and DSN-MUI Fatwa No. 04/DSN-MUI/ IV/2000, and Financial Services Authority Regulation. Secondary data sources are derived from the results of interviews with the Syariah BTPN Bank and the required literature of several journals, theses, and books or books related to the thesis.The results of this study indicate that the Future Package Financing Product Practice at BTPN Syariah Bank is inconsistent with Murabahah regulations on Sharia Economic Law in the MUI DSN fatwa No. 4 of 2000 concerning Murabahah. And there are several indicators of problems that are not in accordance with sharia law. Murabahah transactions carried out by the Bank and customers seem forced to do something that is not in accordance with the Murabahah law itself.